The Marxism of Che Guevara : philosophy, economics, revolutionary warfare - Löwy, Michael (Critical currents in Latin American perspective, 1970)
"In this exploration of Che Guevara's contributions to Marxist thinking, Michael Lowry traces Che's ideas about Marxism as they relate to both Latin America and to more general philosophical, political, and economic issues. Now revised and updated, this edition includes a chapter on Guevara's search for a new paradigm of socialism and a substantive foreword by Peter McLaren on Che's continued relevance today."--BOOK JACKET.